Occupational Stressors and Flourishing among Roman Catholic Priests: The Eucharist as the "Source and Summit" - Upenieks, Laura (Review of religious research, 2024)
The main objective of this study is to examine the trials and tribulations in the lives of priests through an examination of work-related stressors, including feeling disrespected in one’s role as a priest, feelings of overwork, thoughts of leaving the priesthood, and a lack of trust in one’s Bishop, who plays a central role in the daily lives of Catholic priests. This study also assesses how a priest’s relationship with the Eucharist may buffer the effects of these occupational stressors. Drawing from a national sample of priests (N = 3,515), results show that, in order of magnitude, priests who did not feel respected, those thinking of leaving ministry, priests who perceived that their job required them to do things beyond their vocational calling (overwork), and priests with low levels of trust in their bishop all had lower flourishing scores. Eucharistic centrality buffered the deleterious associations between each form of stress and flourishing. Future research on Catholic priests should continue to explore faith-based resources that can promote flourishing across the domains of human life.